2022
DOI: 10.1002/aelm.202100787
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Temperature‐Induced Degradation of Silver Nanowire Electrodes by an Ag@SnOx Core‐Shell Approach

Abstract: diodes, [3] electromagnetic shielding, [4] and organic photovoltaics. [5] Electrodes based on metallic nanowires (NWs) are among the most promising alternatives to indium tin oxide (ITO), which is currently the most efficient and widely used transparent conducting material. [6] Silver, the metal with the highest electrical conductivity, can be expected to provide the best network electrodes. [7] Indeed, silver nanowires (Ag NWs)-based percolating networks successfully combine high flexibility, high optical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The Ag/Cr 2 O 3 NW networks had higher FoM values than Cu nanowire-based ,, TCFs. The optoelectronic characteristics of Ag/Cr 2 O 3 NW networks in this study also compare favorably with some previously reported composite TCFs based on Ag NWs. , Although the FoM of some Ag NWs networks that have been compounded with oxides is higher, the preparation of these networks is time-consuming and expensive. Their widespread use in real-world production is restricted by their expensive price. In contrast, the all-solution method used in this study to grow dense Cr 2 O 3 protective layers on the surface of Ag NWs allows for the growth of these layers under nonvacuum room temperature conditions, lowering processing costs and times, enhancing silver nanowire stability in harsh environments, and obtaining superior optoelectronic performances.…”
Section: Resultssupporting
confidence: 83%
“…The Ag/Cr 2 O 3 NW networks had higher FoM values than Cu nanowire-based ,, TCFs. The optoelectronic characteristics of Ag/Cr 2 O 3 NW networks in this study also compare favorably with some previously reported composite TCFs based on Ag NWs. , Although the FoM of some Ag NWs networks that have been compounded with oxides is higher, the preparation of these networks is time-consuming and expensive. Their widespread use in real-world production is restricted by their expensive price. In contrast, the all-solution method used in this study to grow dense Cr 2 O 3 protective layers on the surface of Ag NWs allows for the growth of these layers under nonvacuum room temperature conditions, lowering processing costs and times, enhancing silver nanowire stability in harsh environments, and obtaining superior optoelectronic performances.…”
Section: Resultssupporting
confidence: 83%
“…Previously reported works on SnO 2 /AgNW nanocomposites show a clear enhancement of thermal and/or chemical stability of AgNW networks. In these studies, chemical vapor deposition and sputtering methods were used to deposit SnO x layers on AgNW networks. None of them have used AP-SALD, except one of our previous work .…”
Section: Resultsmentioning
confidence: 99%
“…This sometimes happens at the expense of performance, leading to lower transmittance, larger electrical resistance or decrease in flexibility . The investigated coatings are often thin layers of metal oxides such as zinc oxide (ZnO), titanium oxide (TiO 2 ), metal oxynitrides (AlO x N y ), or tin oxide (SnO 2 ). In all of these studies, a clear improvement in the stability of the AgNW networks, as well as AgNW adhesion to the substrate, is often reported, thanks to oxide coatings . These coatings are often deposited by spin-coating or by vacuum-based techniques such as atomic layer deposition (ALD) or sputtering and very often exhibit scalability issues for AgNW-based TEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, SnO 2 /AgNW nanocomposites have only been investigated in a few recent articles. 15,[17][18][19][20][21] Several studies have been devoted to investigating the structural properties of AgNWs using X-Ray Diffraction (XRD) measurements under ambient conditions. XRD is a powerful and non-destructive method for studying nanomaterials, 22 particularly during in situ experiments.…”
Section: Introductionmentioning
confidence: 99%